Perancangan Sistem Informasi Kepegawaian Berbasis Web Pada PT Bangun Cipta Anugrah Abadi - Muliawan, Steven; Dafid, Dafid (MDP Student Conference, 2024)
PT. Bangun Cipta Anugrah Abadi is a company operating in the field of house or real estate development. This company has several problems, namely, the company is still not optimal in searching for personnel data so there is a lack of control over personnel data, leave applications are still made with a leave application letter so it is difficult for employees to know the status of the leave that has been applied for. PT. Bangun Cipta Anugrah Abadi requires a personnel information system that can provide convenience for administration and employees in carrying out the process of managing personnel data. This personnel system was created using the RUP (Rational Unified Process) methodology, using the UML (Rational Unified Process) model as a design model, using PHP and JavaScript programming languages, and using supporting applications such as Visual Studio Code, XAMPP, MySQL as DBMS (Database Management System), and CodeIgniter 4 Framework. The results of developing this personnel information system can overcome the problems currently being experienced by PT. Bangun Cipta Anugrah Abadi.